Cryogenic propulsion for the Titan Orbiter Polar Surveyor (TOPS) mission. (March 2016) - Mustafi, S.; DeLee, C.; Francis, J.; Li, X.; McGuinness, D.; Nixon, C.A.; Purves, L.; Willis, W.; Riall, S.; Devine, M.; Hedayat, A.
Highlights: LH2 + LO2 propelled TOPS provides 43% mass savings over a hypergol propelled TOPS. TOPS cryogenic design allows 8.5 years of LO2 passive storage without loss. TOPS cryogen design allows 8.5 years of passive LH2 storage with only 10% LH2 loss. Subcooled LH2 reduces phase change loss by 41% compared to LH2 launched at NBP. LH2 + LO2 enables missions that would not be possible with traditional hypergols. Abstract: Liquid hydrogen (LH2) and liquid oxygen (LO2) cryogenic propellants can dramatically enhance NASA's ability to explore the solar system due to their superior specific impulse ( I sp ) capability. Although these cryogenic propellants can be challenging to manage and store, they allow significant mass advantages over traditional hypergolic propulsion systems and are therefore enabling for many planetary science missions. New cryogenic storage techniques such as subcooling and the use of advanced insulation and low thermal conductivity support structures will allow for the long term storage and use of cryogenic propellants for solar system exploration and hence allow NASA to deliver more payloads to targets of interest, launch on smaller and less expensive launch vehicles, or both. These new cryogenic storage technologies were implemented in a design study for the Titan Orbiter Polar Surveyor (TOPS) mission, with LH2 and LO2 as propellants, and the resulting spacecraft design was able to achieve a 43% launch mass reduction over a TOPS mission, that utilized a traditional hypergolic propulsion system with mono-methyl hydrazine (MMH) and nitrogen tetroxide (NTO) propellants. This paper describes the cryogenic propellant storage design for the TOPS mission and demonstrates how these cryogenic propellants are stored passively for a decade-long Titan mission that requires the cryogenics propellants to be stored for 8.5 years.